Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4314/tjpr.v10i5.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Intake of Fermented Seeds of Parkia biglobosa (Jacq) Benth (African Locust Bean) on Hypertension in Bogou and Goumou-kope Areas of Togo

Abstract: . Conclusion:The results of the present study demonstrate that fermented seeds of Parkia biglobosa exert an anti-hypertension effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Food fermentation as an enterprise is particularly useful in the economy and socio-cultural lives of many communities. The nutritional and socio-economic values, health benefits and functional attributes of fermented foods have been widely documented [62][63][64][65][66][67][68][69][70][71][72][73]. Many of the substrates used for producing fermented foods contain naturally occurring toxins and anti-nutrients and only become edible following detoxification through fermentation.…”
Section: Significance Of Food Fermentation To Rural Communities and Ementioning
confidence: 99%
“…Food fermentation as an enterprise is particularly useful in the economy and socio-cultural lives of many communities. The nutritional and socio-economic values, health benefits and functional attributes of fermented foods have been widely documented [62][63][64][65][66][67][68][69][70][71][72][73]. Many of the substrates used for producing fermented foods contain naturally occurring toxins and anti-nutrients and only become edible following detoxification through fermentation.…”
Section: Significance Of Food Fermentation To Rural Communities and Ementioning
confidence: 99%
“…Seeds, bark, roots and flowers of P. biglobosa are used to treat more than 80 diseases and ailments in West Africa (Ouedraogo, 1995;Nacoulma-Ouedraogo, 1996;Dedehou et al, 2016). Fermented seeds, called "soumbala" or "dawadawa" are used as condiment, which is also well-known for its ability to decrease hypertension (Ognatan et al, 2011). The sweet pulp of pods is a source of energy and nutrients (rich in glucids, proteins, carotenoids, vitamins A, B, C, and oligo-elements), and is important as nutritional and mineral supplement (Omojola et al, 2011;Dahouenon-Ahoussi et al, 2012;Ijarotimi and Keshinro, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Antihypertensive (Assane et al, 1993;Ajaiyeoba, 2000Ajaiyeoba, ), analgesic, antiinflammatory (kouadia et al, 2000, antidiabetic, antidiarrhoeal (Agunu et al, 2005;Odetola et al, 2006) activities of different extracts from P. biglobosa seeds and trees have been reported. Ognatan et al (2011), reported a low incidence of hypertension cases in a community where this condiment is heavily consumed in Togo, within the African continent.…”
Section: Introductionmentioning
confidence: 99%